2016
DOI: 10.1021/acschembio.6b00821
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Bacterial Fucosidase for Glycoprotein Remodeling

Abstract: Fucose is an important component of many oligo- and polysaccharide structures as well as glycoproteins and glycolipids, which are often associated with a variety of physiological processes ranging from fertilization, embryogenesis, signal transduction, and disease progression, such as rheumatoid arthritis, inflammation, and cancer. The enzyme α-l-fucosidase is involved in the cleavage of the fucosidic bond in glycans and glycoconjugates, particularly the Fuc-α-1,2-Gal, Fuc-α-1,3/4-GlcNAc, and Fuc-α-1,6-GlcNAc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…Moreover, the organomercury PCMB severely inactivated the enzyme (Table 1), whereas this inhibitory effect on cFase I was reversible with additional DTT (data not shown). Our observations were similar to those in previous reports on fucosidases (42)(43)(44). Furthermore, the fucosidase-specific inhibitor deoxyfuconojirimycin inhibited the activity of cFase I, indicating the fucosidase activity of the enzyme (Fig.…”
Section: Enzymatic Characterization Of Cfase I With Pnpssupporting
confidence: 93%
“…Moreover, the organomercury PCMB severely inactivated the enzyme (Table 1), whereas this inhibitory effect on cFase I was reversible with additional DTT (data not shown). Our observations were similar to those in previous reports on fucosidases (42)(43)(44). Furthermore, the fucosidase-specific inhibitor deoxyfuconojirimycin inhibited the activity of cFase I, indicating the fucosidase activity of the enzyme (Fig.…”
Section: Enzymatic Characterization Of Cfase I With Pnpssupporting
confidence: 93%
“…However, the increasing abundances of Lactobacillales and Bacteroidales spp. in both groups indicated the hydrolyzing ability of these bacteria on fucoses joined by different linkages, as some studies have revealed the core fucose hydrolyzing abilities of these bacteria (78, 79). Therefore, further molecular mechanical studies regarding to the effects of milk protein N-glycans on these gut microbes are needed.…”
Section: Discussionmentioning
confidence: 92%
“…However, compared with oligosaccharides, the structure of protein N-glycans is more complicated. Bacterium-derived fucosidases were reported to have very low activity in decomposing the α-1,6-bond core fucose (75). Fuc-α1,6-GlcNAc can only be hydrolyzed by α- l -fucosidases with the assistance of endo- N -acetylglucosidases (Endo), which hydrolyzes the N-glycans between two adjacent N-GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, use of synthetic Fuc-α1,6-GlcNAc and Fuc-α1,6-GlcNAc-GlcNAc by L. casei and L. gasseri suggests the coexpression of Endo and AflC-like enzymes in their genomes and their superiority when competing with other gut microbes. However, when Fuc-α1,6-GlcNAc was incubated with Bifidobacterium spp., no obvious growth-promoting effects were detected, although α- l -fucosidase genes were also found in the genomes of Bifidobacterium spp., but with poor activity for hydrolyzing the α1,6-linkage-bond fucose (75). Therefore, the substantially greater proportion of bifidobacteria in infants fed by mothers with high-core-fucosylated milk N-glycan may due to excreted l -fucose by Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%